Four Essays on the Theory of Monetary Policy - Malik, Ali Hamza (My University, 2004)
This dissertation focuses on the construction of macroeconomic models that can be used to evaluate monetary policy. The theoretical models dewloped for this purpose emphasize the importance of intertemporal optimizing behaviour, the role of expectations and nommal price rigidities.
The first essay (chapter 2) compares the implIcations of the interest rate channel and the cost chamlel (when firms' marginal cost depends directly on the nominal interest rate) of the monetary policy transmission mechanism under inflation and price-level targeting regime for determining the optimal trade-off between stabilizing inflation and the output-gap in a forward-looking closed-economy model. In contrast to the traditional literature. which focuses only on the interest rate channel, research presented In chapter 2 demonstrates that the demand shocks cannot be completely stabilized with inflation targeting when the cost channel is operative: the central bank faces an inflation outputgap stabilIzation trade-off. Moreover, it is shown that there are gains (In terms of reduced expected losses for the central bank) to be made from conductIng monetary policy With commitment rather than in a discretionary fashion even if there is no inflation bias. Also. these gains are larger In the presence of cost charmeL so there is a stronger case for commitment.
Furthermore. building on the notion that it is difficult to conduct monetary policy with full commitment due to practical considerations, chapter 2 seeks an answer to the question: Is it possible to replicate the results of inflation targeting under commitment with pnce-Ievel targeting under discretion? The results in chapter 2 confirm the earlier results that it is possible. However, it also points out that the results need to be interpreted carefully in the presence of the cost channel. In particular, the relative weight on outputgap stabilization versus inflation stabilization needs to be appropriately adjusted in comparing the expected value of the losses incurred in the two regimes: otherwise the results could be dIfferent.
Chapter 2 also proposes an altemative method of calculating the implicit interest rate rule that implements the optimal policy. Unlike the existing literature, this method correctly depicts the mertial behaviour of optimal policy with commitment and derives conditions that can avoid indeterminacies of output and inflation. Moreover, in the presence of the cost channel. this method is the only correct method in the commitment case for the sake of intemal consistency of results.
The second essay (chapter 3) uses continuous-time modeling approach instead of the more conventional discrete-time approach and compares the performance of two rulebased targeting regimes --- price-level targeting and nominal income targetmg with and without the cost channel of monetary policy of a closed economy. Chapter 3 considers a senes of macroeconomic models with different specifications for both the aggregate demand side and the aggregate supply side of the economy to check for robustness of results. It is assumed that the two targetmg regimes generate the same outcome regardmg long-term inflation. Thus, the criterion for evaluating the performance of a monetary regime is its ability to minimize the volatIlity in real output in response to aggregate demand shocks.
The main result of chapter 3 is that the cost channel matters in the sense that the volatilIty of real output increases under both price-level and nominal income targetmg when the cost channel is included in the models. However, the inclusion of the cost channel does not say much on the choice between the two regimes. It appears that nominal income targeting performs better than price-level targeting in bringing down the volatility of real output in almost all the specifications of the macro models used in the analysis regardless of the cost channel.
Using the type of models analyzed in chapter 3, chapter 4 introduces open economy considerations and looks at the performance of monetary policy (in terms of reducing volatility in real output) under three altemative targeting regimes: exchange rate targeting (fixed exchange rates), price-Ievel targeting, and nominal income targeting (both flexible exchange rate options). Although the supply-side effects of the interest rate (the cost channel) are Ignored, the supply-side effects of exchange rate changes (due to the existence of intermediate imported inputs) are highlighted.
Under these settings, chapter 4 explores the impact of an increased degree of price flexibility on the volatility of real output. Chapter 4 finds support for Keynes' concern that under a flexible exchange rate regime a higher degree of price flexibility can raise output volatility. This result is consistent with central banks that argue that their low inflation-flexible exchange rate policy has increased contract length and so decreased the degree of nommal price flexibility. Chapter 4 also finds support for central banks that favour fIxed exchange rates. A fixed exchange rate regime implicitly Implies that the economy is willing to accept structural refonns of the sort that promote flexibility m prices to absorb the effects of shocks. Chapter 4 shows that with fixed exchange rates output volatility indeed goes down as a result of increased price flexibility. Thus, there is internal consistency within both views about exchange rate polIcy.
Chapter 5 develops a discrete-tIme dynamic stochastic general equilibrium model with incomplete asset markets. nominal pnce rigidities and monopolistic competItion to shed light on the role of the exchange rate and its relation with current account dynamics and domestic inflation in the formulatton of monetary policy. Chapter 5 argues that the assumption of complete asset markets is not realistic in a model with imperfections and ngidities in goods market because, with nominal rigidities, monetary polIcy wlll affect real variables including the current account. With incomplete asset markets the dynamics of current account does matter for monetary policy because then, besides dealing with the dIstortions created by monopolistic competition, the central bank needs to address the inefficiencies caused by incomplete asset markets.
The main result of chapter 5 is the breakdown of a widely accepted result that optimal monetary policy for an open economy calls for adjusting the interest rate to completely offset demand shocks. which imphes no trade-off between output volatility and inflation volatility. Due to the direct effect of real exchange rate on domestic inflation. the optimal monetary policy calls for trading-off some output volatility for less inflation volatility. Moreover, due to the dynamIcs of current account it entails a response to variations in the net foreign asset position, since this mechamsm makes the impact of the demand shock last well beyond the time interval for which prices are rigid.
Keywords: Economics; Economics